Cold chain and shrimp product quality: impacts on market trust and production management - Samanta, Pinky Natalia; Imroatin, Kholifatul (Indonesian Institute for Counseling, Education and Theraphy, 2025)
Market trust and effective production management are critical factors in maintaining cold chain integrity and ensuring the quality of shrimp products. Reliable cold chain systems directly influence buyer satisfaction and competitive advantage in the seafood export industry. This study aimed to examine the relationship between cold chain management and shrimp product quality, as well as its impact on buyer trust. The research was conducted at a leading shrimp export company, with data collected through temperature monitoring at five critical control points (CCPs), organoleptic and sensory evaluations, buyer satisfaction questionnaires, and semi-structured interviews with internal stakeholders. Descriptive statistics showed varied compliance rates across CCPs, with the lowest at the processing room (21.7%) and washing water (52.8%), both exceeding recommended temperature limits. Correlation analysis revealed a strong positive relationship between cold chain compliance and buyer satisfaction (r = 0.76, p < 0.01), as well as between temperature control and product sensory scores (r = 0.81, p < 0.01). Thematic analysis further highlighted that adherence to SOPs and cross-functional coordination were perceived as crucial for sustaining cold chain performance. These findings contribute to the supply chain management literature by emphasizing the operational role of temperature control in shaping customer trust. Practically, the study recommends that seafood exporters implement real-time temperature monitoring systems and strengthen interdepartmental communication to ensure consistency in cold chain operations and enhance export competitiveness